The theology of suffering and mental distress - Hewitt, Simon (Theology, 2025)
In understanding the intersection of religion and psychopathology it is vital, clinically and philosophically, to attend to internal – theological – perspectives on mental distress. This article explores the Christian theology of mental distress, arguing that there is a tendency to sacralize suffering, in general, and psychological suffering, in particular. Alternative theological perspectives can be appealed to in order to counteract this sacralizing tendency.